2019
DOI: 10.1210/jc.2019-00153
|View full text |Cite
|
Sign up to set email alerts
|

Dose Dependency of Iatrogenic Glucocorticoid Excess and Adrenal Insufficiency and Mortality: A Cohort Study in England

Abstract: Context Adrenal insufficiency and Cushing syndrome are known adverse events of glucocorticoids. However, no population estimates of dose-related risks are available. Objective To investigate dose-related risks of adrenal dysfunction and death in adults with six chronic inflammatory diseases treated with oral glucocorticoids. Design and setting Retrospective, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
54
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 25 publications
1
54
0
3
Order By: Relevance
“…Indeed, overtreatment with GCs is a serious health problem. A recent article showed that GC‐induced Cushing syndrome is more common than tertiary adrenal insufficiency although the author concludes that the low absolute risk of adrenal insufficiency highlights a potential lack of awareness …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, overtreatment with GCs is a serious health problem. A recent article showed that GC‐induced Cushing syndrome is more common than tertiary adrenal insufficiency although the author concludes that the low absolute risk of adrenal insufficiency highlights a potential lack of awareness …”
Section: Discussionmentioning
confidence: 99%
“…However, iatrogenic suppression of the hypothalamicpituitary-adrenal (HPA) axis is an increasing challenge for clinicians 2 . One important factor is the widespread use of novel steroid medications to manage chronic diseases in an ageing society 1,3 . Novel drugs targeting common disorders (for example, hypertension or cancer) interfere with adrenal steroid synthesis or metabolism and have the potential to induce adrenal suppression.…”
mentioning
confidence: 99%
“…To our knowledge, there are no studies in RTR which investigated the association of urinary cortisol metabolism and mortality long‐term after kidney transplantation. However, there are studies in other populations, such as patients with rheumatoid arthritis, pituitary adenoma, acromegaly, and alcoholic hepatitis, showing that treatment with higher doses of corticosteroids is associated with an increased risk of mortality.…”
Section: Discussionmentioning
confidence: 99%